2022
DOI: 10.21037/jgo-22-348
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant treatment for the elderly patient with resected gallbladder cancer: a SEER-Medicare analysis

Abstract: Background: In patients with resected gallbladder cancer (GBC), the role of adjuvant chemotherapy (aCT) remains ill-defined, especially in elderly patients. This study evaluates the value of aCT in elderly patients with GBC and assesses response according to tumor stage.Methods: Patients of ≥65 years of age with resected GBC diagnosed from 2004-2015 were identified using a Surveillance, Epidemiology and End Results (SEER)/Medicare linked database. After propensity score matching, survival of patients treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Furthermore, the latter study included patients diagnosed within an earlier period (2004-2011). Nevertheless, in an investigation of the Surveillance, Epidemiology, and End Results and Medicare–linked database of patients aged 65 years or older with resected GBC, similar to our report, only 25% of patients received AC, and this did not provide a survival benefit over observation (median OS, 17.6 vs 19.5 months; P = .77) . Another analysis of NCDB data concluded that adjuvant therapy was associated with improved survival for hilar cholangiocarcinoma (40.0 vs 30.6 months; P = .03) but not distal cholangiocarcinoma (33.0 vs 30.3 months; P = .12) .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Furthermore, the latter study included patients diagnosed within an earlier period (2004-2011). Nevertheless, in an investigation of the Surveillance, Epidemiology, and End Results and Medicare–linked database of patients aged 65 years or older with resected GBC, similar to our report, only 25% of patients received AC, and this did not provide a survival benefit over observation (median OS, 17.6 vs 19.5 months; P = .77) . Another analysis of NCDB data concluded that adjuvant therapy was associated with improved survival for hilar cholangiocarcinoma (40.0 vs 30.6 months; P = .03) but not distal cholangiocarcinoma (33.0 vs 30.3 months; P = .12) .…”
Section: Discussionsupporting
confidence: 72%
“…Nevertheless, in an investigation of the Surveillance, Epidemiology, and End Results and Medicare-linked database of patients aged 65 years or older with resected GBC, similar to our report, only 25% of patients received AC, and this did not provide a survival benefit over observation (median OS, 17.6 vs 19.5 months; P = .77). 18 Another analysis of NCDB data concluded that adjuvant therapy was associated with improved survival for hilar cholangiocarcinoma (40.0 vs 30.6 months; P = .03) but not distal cholangiocarcinoma (33.0 vs 30.3 months; P = .12). 19 Another interesting but not surprising finding in this study was that single-agent AC provided an improvement in median OS compared with observation and multiagent AC, which may reflect the ineffectiveness of the combination therapy regimens that have been used in the adjuvant setting to date.…”
Section: Jama Network Open | Oncologymentioning
confidence: 99%